House : modern diversity - Veteewootacharn, Kiattisak, editor (Singapore : Page One, 2013)
The book features several designs for private residences by Architects 49 House Design (A49HD) within the past few years. Richly illustrated and designed with the same care that the architects give to their work, this collection demonstrates the simultaneous play of form and attention to detail that allows A49 HD to create residences of the highest distinction. Part of the larger A49 Group, the work in this volume clearly demonstrates a continuing excellence, with the clean sharp lines of ultra-modern forms softened by a rich pallete of materials, with the masterful interplay of water, stone, steel, concrete and wood, and with the constant interplay of solid and void that allows continuity between the overlapping volumes of interior and exterior